Preventing SOx Emissions through Process Control: Interdigital Capacitors for On-Site Monitoring of Thiophene-Based Environmental Pollutants in Oil Refineries. Issue 9 (9th September 2021) - Irshad, Muhammad; Afzal, Adeel; Mujahid, Adnan; Bajwa, Sadia Z.; Hussain, Tajamal; Zaman, Waheed-Uz; Latif, Usman; Din, Muhammad Imran; Ali, Farman; Iqbal, Naseer
Abstract : The presence of organosulfur compounds in fossil fuels is a major source of environmental pollution (SOx emissions) and deteriorates the catalytic exhaust systems of automobiles. Therefore, the development of miniaturized, low-cost, robust interdigital capacitors (IDC) is required to precisely monitor organosulfur compounds in petroleum products. Based on the Pearson concept of hard/soft acids/bases (HSAB), NiS nanoparticles were prepared and integrated into chemical, heat, and wear-resistant TiO2 coatings to fabricate sensitive layers on IDC for the detection of benzothiophene (BT) and dibenzothiophene (DBT) in gasoline samples. Compared to NiS nanoparticles and pristine TiO2 sol, TiO2 -NiS nanocomposites exhibit distinctive morphology with homogeneous distribution of NiS nanoparticles, high surface roughness, and greater localized nanoscale variations. Therefore, HSAB chemistry and spatially distinctive features of TiO2 -NiS/IDC sensors yield excellent response and sensitivity toward BT/DBT. The reproducibility of sensor layers, selectivity, repeatability, and stability of TiO2 -NiS/IDC sensor were studied before calibrating the devices for real-time measurements in refined gasoline samples. TiO2 -NiS/IDC sensors exhibit a wide-range linear response, high sensitivity, and low detection limits in gasoline. Real-time sensor measurements show a 90.7% recovery of BT/DBT from gasoline samples. The sensors were calibrated in gasoline samples for potential process and quality control applications during crude oil refining.